Effects of mannose-binding lectin and mannose-binding lectin polymorphisms on treatment response in patients with chronic hepatitis C - Kömür, Süheyla; İnal, Ayşe Seza; Candevir Ulu, Aslıhan; Kurtaran, Behice; Taşova, Yeşim; Salih, Hasan; Aksu, Zeki (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: The natural course and clinical outcome of hepatitis C virus (HCV) infection is related to the interaction between HCV and the immune response of the host. Only a limited number of studies have investigated the role of mannose-binding lectin (MBL) levels in HCV infection. The aim of the present study was to explore the relationship between MBL levels and gene polymorphisms on treatment response in patients with chronic hepatitis C (CHC). Materials and Methods: Serum MBL levels from 50 CHC patients who completed treatment at least 24 weeks before the present study and 75 healthy HCV-negative controls were measured. In addition, the presence of codon 54 mutations was investigated. Correlational analyses were performed to determine relationships between MBL levels and treatment response. Results: In patients, mean serum MBL levels were lower and the rate of codon 54 mutations was higher. However, these differences were not statically significant. In both patients and controls, serum MBL levels were significantly lower in individuals with codon 54 mutations. Moreover, serum MBL levels and the rate of the codon 54 mutation were similar in patients regardless of treatment response. Conclusion: Our findings suggest that low MBL levels do not increase the susceptibility for HCV infection. Furthermore, MBL levels were not found to have a significant effect on the course of the disease or treatment response.